A new species of the genus Mystriophis (Anguilliformes: Ophichthidae) from Cabo Verde (Eastern Central Atlantic), with notes on two Mystriophis specimens documented on the R/V Dr. Fridtjof Nansen - Luz, Alciany Nascimento Da; Correia, Sandra Margarida; Lopes, Evandro P.; Jimenez, Jose Gonzalez; Traore, Diafodé; Psomadakis, Peter Nick (Zootaxa, 2025)
A new species of spoon-nose eel, Mystriophis caboverdensis sp. nov., is described from the Cabo Verde Archipelago based on a single adult specimen (723 mm TL). It co-occurs in the tropical eastern Atlantic with two similar looking species, M. rostellatus (Richardson) and M. crosnieri Blache. The new species is distinguished from both congeners by its uniquely advanced position of the dorsal fin origin, the inner and outer maxillary teeth subequal in size, shorter head and predorsal length, fewer pectoral fin rays, more lateral-line pores, along with vertebral formula, and body colouration. The COI sequences of the new species and M. crosnieri (746 mm TL) collected off the Guinean coast are provided for the first time, with a clear genetic divergence (p-distance=3.6%) between the two species. A photographic record of a large Mystriophis (1022 mm TL) from São Tomé, tentatively identified as M. cf. rostellatus, is also presented with a revised key to species of the genus Mystriophis.